Sweden after Nazism politics and culture in the wake of the Second World War - Östling, Johan 1978- (Berghahn, 2016)
"As a nominally neutral power during the Second World War, Sweden in the early postwar era has received comparatively little attention from historians. Nonetheless, as this definitive study shows, the war...and particularly the specter of Nazism...changed Swedish society profoundly. Prior to 1939, many Swedes shared an unmistakable affinity for German culture, and even after the outbreak of hostilities there remained prominent apologists for the Third Reich. After the Allied victory, however, Swedish intellectuals reframed Nazism as a discredited, distinctively German phenomenon rooted in militarism and Romanticism. Accordingly, Swedes' self-conception underwent a dramatic reformulation. From this interplay of suppressed traditions and bright dreams for the future, postwar Sweden emerged"...From publisher's website
Originally published as Nazismens sensmoral : Svenska erfarenheter i andra världskrigets efterdyning (Stockholm : Atlantis, 2008). - Includes bibliographical references and index
Keywords: Geschichte 1900-2000; Geschichte 1945-1955; Geschichte; Gesellschaft; Politik; Weltkrieg (1939-1945); Politics and culture -- Sweden -- History -- 20th century; War and society -- Sweden -- History -- 20th century; National socialism -- Sweden -- History -- 20th century; Nazis -- Sweden -- History -- 20th century; Social change -- Sweden -- History -- 20th century; World War, 1939-1945 -- Social aspects -- Sweden; World War, 1939-1945 -- Influence; Vergangenheitsbewältigung; Nationalsozialismus; Deutschland; Schweden; Sweden -- Politics and government -- 1905-1950; Sweden -- Relations -- Germany; Germany -- Relations -- Sweden